Effect of a comprehensive ambulatory care model on outcomes of patients with acute coronary syndrome in Colombia - Dagnovar Aristizábal; Jaime Gallo; Ángela Valencia; Juan Jaime; Mónica Correa; Alberto Aristizábal; Marcela Montoya; José Abad
OBJECTIVE: To evaluate the effect of a care program designed according to a comprehensive ambulatory care model (CACM) on the appearance of new cardiovascular/coronary events in patients with acute coronary syndrome. METHODS: Participants in this quasi-experimental intervention study included acute coronary syndrome patients 30-70 years old. The intervention group (n = 165) received care under the CACM, guided by an interdisciplinary team. The CACM included transitional care, risk stratification by severity, physiological profiling (impedance cardiography), and a treatment plan in accordance with current guidelines. The control group (n = 277) received conventional, recommended care in an ambulatory cardiac rehabilitation program. During one year of follow-up, the use of emergency and hospital services related to new cardiovascular and coronary events was evaluated. RESULTS: Differences in the numbers of cardiovascular events (P = 0.003) and coronary events (P = 0.006) experienced by patients were found between the control group and the intervention group. The instantaneous risk of a cardiovascular event (hazard ratio (HR) = 1.80; 95% confidence interval (CI): 1.17-2.75; P = 0.007) and of a coronary event (HR = 1.81; 95% CI: 1.13-2.90; P = 0.013), after adjusting for age, sex, smoking, and compromised coronary arteries, was higher in the control group than the intervention group. CONCLUSIONS: Provision of care under the CACM to patients who had experienced an acute coronary event reduced emergency room visits and rehospitalizations related to new cardiovascular and coronary events by 40%. The average "number needed to treat" (NNT) under the CACM to have an impact on one person (in this case, the prevention of one cardiovascular or coronary event), was 9 and 11 respectively, indicating it is cost-effective.